On the chemical homogeneity of InxGa1−xN alloys – Electron microscopy at the edge of technical limits. (July 2017) - Specht, Petra; Kisielowski, Christian
Abstract: Ternary Inx Ga1−x N alloys became technologically attractive when p-doping was achieved to produce blue and green light emitting diodes (LED)s. Starting in the mid 1990th, investigations of their chemical homogeneity were driven by the need to understand carrier recombination mechanisms in optical device structures to optimize their performance. Transmission electron microscopy (TEM) is the technique of choice to complement optical data evaluations, which suggests the coexistence of local carrier recombination mechanisms based on piezoelectric field effects and on indium clustering in the quantum wells of LEDs. We summarize the historic context of homogeneity investigations using electron microscopy techniques that can principally resolve the question of indium segregation and clustering in Inx Ga1−x N alloys if optimal sample preparation and electron dose-controlled imaging techniques are employed together with advanced data evaluation.